Evaluating the Adequacy of Central Line-Associated Bloodstream Infection As a Quality Measure: A Cross-Sectional Analysis at a Single Tertiary Care Center - Piyush Mathur, MD, FCCM, FASA, FAMIA; Amanda J. Naylor, MD, MPH; Moises Auron, MD; Jean Beresian, MD; Alexandra Tallman, BSN, RN, SANE-A; Allison Griffith, MSN, RN, CCRN, CPHQ; Kathleen Seasholtz, BSN, RN, HACP; Mariel Manlapaz, MD; Katherine Zacharyasz, MSN, RN, CPHQ; Reem Khatib, MD, MBA, FASA; Shreya Mishra, PhD; Kathryn Haller, PA; et al. (Critical Care Explorations)
IMPORTANCE:. The current definition of central line-associated bloodstream infection (CLABSI) may overestimate the true incidence of CLABSI as it is often unclear whether the bloodstream infection (BSI) is secondary to the central line or due to another infectious source. OBJECTIVES:. We aimed to assess the prevalence and outcomes of central CLABSI at our institution, to identify opportunities for improvement, appropriately direct efforts for infection reduction, and identify gaps in the CLABSI definition and its application as a quality measure. DESIGN, SETTING, AND PARTICIPANTS:. Retrospective cross-sectional study of patients identified to have a CLABSI in the period 2018–2022 cared for at the value-based purchasing (VBP) units of a 1200-bed tertiary care hospital located in Cleveland, OH. Each CLABSI episode was assessed for relationship with central venous catheter (CVC), suspected secondary source of BSI, mortality associated with the CLABSI hospital encounter, and availability of infectious disease physician or primary physician documentation of infectious source. MAIN OUTCOMES AND MEASURES:. CLABSI episodes were classified as CVC related, CVC unrelated, and CVC relationship unclear. Mortality during the same encounter as the CLABSI event was assessed as an outcome measure. Descriptive statistics were performed. RESULTS:. A total of 340 CLABSI episodes occurred in adult patients in VBP units. Majority of the CLABSI, 77.5% (266), occurred in the ICU. Of the CLABSI analyzed, 31.5% (107) were classified as unrelated to the CVC; 25.0% (85) had an unclear source; 43% (148) were classified as CVC related. For CVC-related cases, Staphylococcus and Candida were the predominant organisms. For the CVC unrelated and unclear groups Enterococcus was most prevalent. The mortality rate was lowest among patients classified with a CVC-related BSI. The positive predictive value (PPV) of the Centers for Disease Control and Prevention CLABSI definition to predict a true CVC-related infection was found to be 58.0%. CONCLUSIONS AND RELEVANCE:. The definition of CLABSI as a surrogate for catheter-related BSI is inadequate, with a PPV of 58.0% (43.1–67.6%). Efforts should be redirected toward revising the CLABSI definition and possibly reevaluating its criteria. Resources should be assigned to further investigate and systematically prevent BSIs from secondary sources while adhering to existing CLABSI prevention bundles.